Femorodistal bypasses using venous “cuffs” - Sekulić, Dragan; Marjanović, Ivan; Leković, Ivan; Paunović, Dragana; Milev, Boško; Tomić, Aleksandar (Vojnosanitetski pregled, 2023)
Background/Aim. Although distal venous patch and cuff techniques are recommended to improve the patency of by-pass in the lower extremities, the advantage of these tech-niques remains unproven. Autovenous bypass graft remains the method of choice, but when there is no possibility of us-ing the great saphenous vein, the venous cuff method may have an advantage. The aim of this study was to evaluate the results of femorodistal bypass procedures with a venous cuff in critical lower extremity ischemia. Methods. The study de-scribed the results of femorodistal bypass procedures after a follow-up period of 6 to 24 months. We followed 28 patients with distal composite anastomosis of femorodistal arterial re-construction. Indications for surgical treatment were set on the basis of the clinical exam and morphological criteria based on multidetector computed tomographic angiography. Three types of distal graft-arterial anastomoses were applied: Miller’s cuff, Taylor’s patch, and St. Mary’s vein boot anastomosis. Results. After 6 months of surgery, all bypasses were passa-ble; after one year, 2 (7%) patients had graft occlusion and above-knee amputation, and 8 (28%) patients died; after 24 months, 18 (64%) patients had primary bypass patency. Con-clusion. Femorodistal bypass procedures using a synthetic graft and venous cuff have good long-term results. The opti-mal anastomosis type is St. Mary’s boot. A longer follow-up period and comparison with the autovenous bypass are nec-essary for a more detailed assessment of the final conclusion.